Availability of illicit tobacco in small retail outlets before and after the implementation of Australian plain packaging legislation. Issue Volume 24:Issue e1(2015) (10th April 2014) - Scollo, Michelle; Bayly, Megan; Wakefield, Melanie
Abstract : Objective: We aimed to assess change in the availability of illicit tobacco in small mixed business retail outlets following the December 2012 introduction of plain packaging in Australia. Methods: 303 small retail outlets were visited in June and September 2012 (baseline months), and in December 2012 and February, April and July 2013. Fieldworkers requested a particular low-cost brand of cigarettes and then pressed the retailer for an 'even cheaper' brand. The cheapest pack of cigarettes offered was purchased and later examined to assess any divergence from prescribed Australian packaging regulations. The price paid was compared with tax liability and recommended retail price for the particular brand and pack size. In a sub-set of 179 stores, fieldworkers then asked the retailer about availability of unbranded (chop-chop) tobacco. Results: Thirteen (2.2%) of 598 packs purchased pre-plain packaging were either non-compliant with Australian health warnings and/or suspiciously priced. Four packs (1.3%) of 297 met either or both criteria in the December implementation month, and five (0.6%) of 878 did so in the three collection months following implementation. Chop-chop was offered upon enquiry on 0.6% (n=2) of 338 occasions prior to implementation, 0.6% (n=1) of 170 occasions in the December 2012 implementation month, and 0.6% (n=3) of 514 occasions postimplementation. The likelihood of a 'positive' response (either an offer to sell or information about where unbranded tobacco may be purchased) did not differ across preimplementation, during-implementation and postimplementation waves. Conclusions: Overall, packs judged likely to be illicit were sold in response to requests for cheapest available packs on fewer than one percent of occasions. Offers to sell unbranded tobacco were rare. No change in availability of illicit tobacco was observed following implementation of plain packaging.